Peningkatan Kemampuan Membaca Percakapan Singkat Melalui Strategi Role Playing dengan Media Cerita Bergambar pada Siswa Kelas V SDN Majegan 3 Tahun 2015/2016 - Fitriyati, Nurul; , Dra. Ratnasari Diah Utami, M.Si., M.Pd (2016)
This study aims to increase the reading ability a short conversation through role playing strategy with media picture stories fifth grade students of Majegan 3 Elementary School. This type of research is a classroom action research (CAR). The subjects in this study were teachers and fifth grade students of Majegan 3 Elementary School with fourteen students. While the object of research is reading ability a short conversation by applying role playing strategy with media picture story. The technique of collecting data through interviews, observation, testing and documentation. Data analysis technique used triangulation techniques. The results showed an increased reading ability a short conversation of students that includes four aspects of indicators of reading ability, which includes: pronunciation and intonation at pre cycle 62.50%, the first cycle increased 67% and 91% in the second cycle, ability to leave comments and reasons in pre cycle 55%, the first cycle 79% and increased in the second cycle 89%, use of punctuation in the pre cycle 55%, the first cycle 82% and increased in the second cycle 86%, understanding the story on the pre cycle 55%, the first cycle 77% and increased in the second cycle 91%. Strategy Role Playing with media picture story also increased student learning outcomes at the stage of pre-cycle there are 6 students who completed KKM or 43% and increased in the second cycle there are 14 students who completed the KKM or 100%. The conclusion of this study is through the application of Role Playing Strategy with media picture stories can increase the reading ability a short conversation fifth grade students of Majegan 3 Elementary school of school year 2015/2016.